1985
DOI: 10.1002/clc.4960080703
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function after elective aneurysmectomy

Abstract: Summary:Employing rest and exercise first-pass radionuclide angiography before and 3 months after surgery, we studied patients with hemodynamically stable left ventricular aneurysm (LVA) undergoing both coronary artery bypass surgery to relieve angina pectoris and elective aneurysmectomy. There were 15 patients, 14 men and 1 woman with a mean age of 54f7 years. All patients had anterior and/or apical LVA. After surgery the postexercise mean left ventricular ejection fraction (LVEF) for the whole group improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The mortality rate was significantly higher for patients with LVA [1][2][3][4] owing to a higher incidence of complications such as ventricular arrhythmias, 23 thromboembolic phenomena, 24 and congestive heart failure. 25 Moreover, Meizlish et al 26 reported that LVA carries a high risk of mortality independent of left ventricular ejection fraction. Therefore, it is reasonable to predict which patients will have LVA after acute MI, and HRV analysis on day 5 may help the clinician to define the patients with a high risk for developing LVA.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate was significantly higher for patients with LVA [1][2][3][4] owing to a higher incidence of complications such as ventricular arrhythmias, 23 thromboembolic phenomena, 24 and congestive heart failure. 25 Moreover, Meizlish et al 26 reported that LVA carries a high risk of mortality independent of left ventricular ejection fraction. Therefore, it is reasonable to predict which patients will have LVA after acute MI, and HRV analysis on day 5 may help the clinician to define the patients with a high risk for developing LVA.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike patients with ischemic cardiomyopathy and congestive heart failure in whom bypass graft surgery is not helpful,59 the presence of LVA in a patient with severe congestive heart failure is an indication for surgery. 60,61 Contrast ventriculography and other noninvasive methods can help differentiate between the two entities in the patient with coronary artery disease and congestive heart failure. These tests can also help predict operative risk and improvement in functional class.…”
Section: Congestive Heart Failurementioning
confidence: 99%
“…Left ventricular aneurysm (LVA) secondary to acute myocardial infarction (AMI) can lead to a poor prognosis. Heart failure [1] is the most common cause of death in patients with LVA duo to severe left ventricle (LV) remodeling. Surgical repair is still the optimal therapy for LVA.…”
Section: Introductionmentioning
confidence: 99%